A Special Safeguard Mechanism for Agricultural Imports and the Management of Reform - Finger, J. Michael (2012)
The record of traditional safeguard provisions of the General Agreement on Tariffs and Trade and the World Trade Organization provides useful information about how a special agricultural safeguard might be made effective. The success of existing safeguard or flexibility provisions to sustain long-run liberalization programs stems from their requiring objective, transparent, and participatory decisions on the application of the import restrictions they allow. The proposed special agricultural safeguard expands by arithmetic formula the bounds within which a Member may impose a new import restriction. Analysis reported here suggests that the formulas provide a poor guide for policy, indicating that they would frequently prescribe action that is not needed and fail to prescribe action when it would be appropriate. Analysis of the existing agricultural safeguard, to which the special agricultural safeguard is similar, indicates that it has functioned not as an allowance for occasional response to unusual situations but as an expansion of the limits Members have accepted through tariff bindings. To be useful, the special agricultural safeguard should do more than provide formulas for import restrictions. It should provide for objective and participatory processes that would bring forward relevant information and guide an objective and balanced accounting of the interests at play.